1970
DOI: 10.1111/j.1365-3180.1970.tb00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Pyrazon and Benzthiazuron in Sugar Beet

Abstract: Summary. Pyrazon (5‐amino‐4‐chloro‐2‐phenylpyridazin‐3(2H)‐one) and benzthiazuron (N‐(2‐benzothiazolyl)‐N′‐methylurea) were compared in respect to their effects on photosynthesis and growth of sugar beet, and to their movement in soil. Benzthiazuron had a five‐fold greater inhibitory effect than pyrazon on photosynthesis, and a ten‐fold greater inhibitory effect on the growth of sugar beet grown in treated culture solution. On the other hand, sugar beet was more tolerant to benzthiazuron than to pyrazon when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The scope of the reactivity of 4 has also been extended to a variety of other nucleophile classes to give biologically relevant molecules in good to excellent yields (Table ). Among these are anticonvulsant carbamate 7 , thiocarbamates 8 and 9 investigated for their nematicidal and antimycotic activities, respectively, and benzthiazuron ( 10 ), a potent broad leaf and grass herbicide derived from 2-aminobenzthiazole. The lack of reactivity of 4 with alcohols had previously been displayed in the reaction of ephedrine (Table , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…The scope of the reactivity of 4 has also been extended to a variety of other nucleophile classes to give biologically relevant molecules in good to excellent yields (Table ). Among these are anticonvulsant carbamate 7 , thiocarbamates 8 and 9 investigated for their nematicidal and antimycotic activities, respectively, and benzthiazuron ( 10 ), a potent broad leaf and grass herbicide derived from 2-aminobenzthiazole. The lack of reactivity of 4 with alcohols had previously been displayed in the reaction of ephedrine (Table , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…The site of entry of the two herbicides from the soil to pepper seedlings was studied by a technique described elsewhere (Eshel & Sompolinsky, 1970). Diphenamid and napropamide were applied in concentrations of 50 ppm and 25 ppm, respectively, to either the root or the shoot zone of the soil.…”
Section: Site Of Uptakementioning
confidence: 99%
“…Leaching experiments were carried out in soil columns by a technique described previously (Eshel & Sompolinsky, 1970). Depth of leaching of 2-5 and 5-0 kg/ha of the herbicides into sandy soil by 5 cm of simulated rainfall was determined in bioassays with oats in the various soil layers.…”
Section: Mobility In Soilmentioning
confidence: 99%
“…Prendeville (1968) found, however, that in maize the shoot region around the growing point and crown root node was most sensitive to propham, chlorpropham and EPTC. Prendeville et al (1967), Eshel (1969), Eshel & Sompolinsky (1970) and Walker (1973) demonstrated that various herbicides which inhibit photosynthesis are more effective when present at the root zone.…”
Section: Introductionmentioning
confidence: 99%